EFFECT OF PATIENT EDUCATION COMBINED WITH PHYSIOTHERAPY TREATMENT ON FEAR-AVOIDANCE BELIEF IN LOW BACK PAIN SUFFERERS - ZARINA ZAHARI,; KAMARIA KAMARUDDIN,; IDA ROSMINI OTHMAN,; MARIA JUSTINE, (International Journal of Pharma and Bio Sciences, 2014)
Fear-avoidance beliefs is one of the factors contribute to low back pain. The study was to determine the effect of patient education combined with physiotherapy treatment on fear-avoidance beliefs for low back pain using Fear-Avoidance Beliefs Questionnaire (FABQ). A quasi-experimental study with 100 participants was randomly assigned into 2 groups. The experimental group received the education and physiotherapy treatment whereas the control group only received the physiotherapy treatment. Both physical and work components of FABQ showed non-significant main effects on group respectively [F(1, 98) =.36, p= .55, η2 = .004]; [F(1, 98) =.88, p= .35, η2 = .009]. However, the study demonstrated minimal effects in the experimental group as compared to the control. This study might assist to reduce the fear-avoidance beliefs in low back pain.